Analysis of the Stress Load Distribution Equation on an Elastic Soil Layer - Simangunsong, Sumihar; Naibaho, Bonar S.M.; Pangaribuan, Melva E. (Lembaga Komunikasi dan Informasi Dosen, 2025)
This research is based on showing how the relationship of differential equation analysis methods to obtain the pressure distribution function on the soil. The purpose of this research is to show how the differential pressure equation is analyzed to obtain the pressure distribution function. This research is a qualitative research. The place of this research is at the TD Pardede Institute of Science and Technology. From the results of the analysis in this study, it was fo und that the application of load pressure on the soil can result in soil consolidation. The process of soil consolidation is an event in the form of soil compression caused by the load above it or the soil load itself. This event also causes an increase in the shear strength of the soil. However, if the load pressure exceeds the limit of the morh value, the potential of the soil will experience a shift (displacement). In the case of isotropic theory in soil mechanics which is used to calculate the vertical stress distribution in the soil due to external loads, such as foundation loads. This theory assumes that the soil is elastic, homogeneous, isotropic, and does not experience a change in volume before being loaded.